Black-blood native T1 mapping: blood signal suppression for reduced partial voluming in the myocardium - Weingärtner, Sebastian; Zöllner, Frank G.; Schad, Lothar R. (Magnetic resonance in medicine, 2017)
Purpose To study the feasibility of black-blood contrast in native T1 mapping for reduction of partial voluming at the blood-myocardium interface. Methods A saturation pulse prepared heart-rate-independent inversion recovery (SAPPHIRE) T1 mapping sequence was combined with motion-sensitized driven-equilibrium (MSDE) blood suppression for black-blood T1 mapping at 3 Tesla. Phantom scans were performed to assess the T1 time accuracy. In vivo black-blood and conventional SAPPHIRE T1 mapping was performed in eight healthy subjects and analyzed for T1 times, precision, and inter- and intraobserver variability. Furthermore, manually drawn regions of interest (ROIs) in all T1 maps were dilated and eroded to analyze the dependence of septal T1 times on the ROI thickness. Results Phantom results and in vivo myocardial T1 times show comparable accuracy with black-blood compared to conventional SAPPHIRE (in vivo: black-blood: 1562 ± 56 ms vs. conventional: 1583 ± 58 ms, P = 0.20); Using black-blood SAPPHIRE precision was significantly lower (standard deviation: 133.9 ± 24.6 ms vs. 63.1 ± 6.4 ms, P < .0001), and blood T1 time measurement was not possible. Significantly increased interobserver interclass correlation coefficient (ICC) (0.996 vs. 0.967, P = 0.011) and similar intraobserver ICC (0.979 vs. 0.939, P = 0.11) was obtained with the black-blood sequence. Conventional SAPPHIRE showed strong dependence on the ROI thickness (R2 = 0.99). No such trend was observed using the black-blood approach (R2 = 0.29). Conclusion Black-blood SAPPHIRE successfully eliminates partial voluming at the blood pool in native myocardial T1 mapping while providing accurate T1 times, albeit at a reduced precision.